2011
DOI: 10.1124/dmd.111.043562
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Figopitant and Its Metabolites in Rat Tissue by Combining Whole-Body Autoradiography with Liquid Extraction Surface Analysis Mass Spectrometry

Abstract: ABSTRACT:This article describes the combination of whole-body autoradiography with liquid extraction surface analysis (LESA) and mass spectrometry (MS) to study the distribution of the tachykinin neurokinin-1 antagonist figopitant and its metabolites in tissue sections of rats after intravenous administration of 5.0 mg/kg figopitant. An overview of autoradiography results is presented together with mass spectrometry identification and semiquantification of parent drug and its metabolites based on LESA-MS. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Additional studies have shown LESA to provide semi-quantitative distribution data for drugs and their metabolites, which was in agreement with quantitative WBA [107,108].…”
Section: Lesasupporting
confidence: 61%
“…Additional studies have shown LESA to provide semi-quantitative distribution data for drugs and their metabolites, which was in agreement with quantitative WBA [107,108].…”
Section: Lesasupporting
confidence: 61%
“…84 Such “contact” model LESA may be advantageous for the analysis of samples containing a protective layer on the surface. When installed on a fully automated robotic system, it enables high-throughput, spatially resolved analysis of metabolites, 85,86 lipids, 8790 and proteins 91,92 in complex samples, including dried blood spots, 84,88 contact lenses, 89 tissues, 55,83,86,91 and microbial colonies. 84,93 LESA also has been used for analyzing molecules separated using TLC 83 and capillary electrophoresis.…”
Section: Ambient Liquid Extraction Techniquesmentioning
confidence: 99%
“…86 While autoradiography enabled quantitative high-resolution imaging of the labeled figopitant, it could not distinguish between the drug and drug metabolites as both contained the isotopic label. LESA MS proved to be superior for the identification of drug and drug metabolites.…”
Section: Localized Analysis and Imaging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This challenge is perfectly suited for liquid extraction-based surface sampling probes [8] that have been successfully used with MS for detecting drugs [9] and Phase I [10][11][12], and II metabolites [13][14][15][16][17][18] from animal thin tissue sections. More importantly, integration with HPLC-MS/MS systems was accomplished for both the sealing surface-sampling probe [19,20] and various liquid microjunction surface-sampling probe configurations [16][17][18] to increase sensitivity of the analyses.…”
Section: Introductionmentioning
confidence: 99%